Application of metabolomics in sarcoma: From biomarkers to therapeutic targets. (August 2017) - Min, Li; Choy, Edwin; Tu, Chongqi; Hornicek, Francis; Duan, Zhenfeng
Highlights: Metabolomics technology is able to comprehensively determine the entire metabolome present in a sarcoma sample. Metabolomics studies have revealed distinct metabolic pathways associated with cell proliferation, invasion/migration, drug resistance in sarcoma. Metabolomics offers an innovative strategy to identify new diagnostic, predictive and prognostic biomarkers, as well as treatment targets in sarcoma.